Principle methods of assessing concurrent delays in construction - Purnomo, 1984-; Norazam Othman, supervisor; Fakulti Alam Bina (2012)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2012